Endoscopic ultrasound-guided fine-needle aspiration plus KRAS and GNAS mutation in malignant intraductal papillary mucinous neoplasm of the pancreas - Bournet, Barbara; Vignolle-Vidoni, Alix; Grand, David; Roques, Céline; Breibach, Florence; Cros, Jérome; Muscari, Fabrice; Carrère, Nicolas; Selves, Janick; Cordelier, Pierre; Buscail, Louis (Endoscopy International Open, 2016)
Background:KRAS and GNAS mutations are common in intraductal papillary mucinous neoplasia of the pancreas (IPMN). The aims of this study were to assess the role of pre-therapeutic cytopathology combined with KRAS and GNAS mutation assays within cystic fluid sampled by endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) to predict malignancy of IPMN. Patients and methods: We prospectively included 37 IPMN patients with clinical and/or imaging predictors of malignancy (men: 24; mean age: 69.5 years). Cytopathology (performed on cystic fluid and/or IPMN nodules), KRAS (Exon 2, codon 12) and GNAS (Exon 8, codon 201) mutations assays (using TaqMan® allelic discrimination) were performed on EUS-FNA material. The final diagnosis was obtained from IPMN resections (n = 18); surgical biopsies, EUS-FNA analyses, and follow-up (n = 19): 10 and 27 IPMN were benign and malignant, respectively.Results: Sensitivity, specificity, positive and negative predictive values, and accuracy of cytopathology alone to diagnose IPMN malignancy were 55 %, 100 %, 100 %, 45 %, and 66 %, respectively. When KRAS-mutation analysis was combined with cytopathology these values were 92 %, 50 %, 83 %, 71 %, and 81 %, respectively. GNAS assays did not improve the performances of cytopathology alone or those of cytopathology plus a KRAS assay.Conclusions: In patients with a likelihood of malignant IPMN at pre-therapeutic investigation, testing for KRAS mutations in cystic fluid sampling by EUS-FNA improved the results of cytopathology for the diagnosis of malignancy whereas GNAS mutation assay did not.